Analisis Perundungan terhadap Tokoh Herlina dalam Film Munkar Melalui Perspektif Sosiologi Sastra - Rena Novitasari; Raras Hafiidha Sari (Pusat Riset dan Inovasi Nasional, 2024)
This research is motivated by the rampant cases of bullying that occur in Indonesia. This study links bullying in the film Munkar with the sociological study of Ian Watt's literature. The purpose of this study is to describe bullying that correlates with Ian Watt's theory. The results of this study are the discovery of bullying experienced by Herlina and the existence of bullying cases at elementary, junior high, high school, Islamic boarding schools, and even in college to strengthen the concept of Ian Watt's theory that is described. https://www.threshingbee.org/https://bradcoweb.com/https://rugsforyourhome.com/https://airportautorvpawn.com/https://slovakbeer.com/https://funnybrideguide.com/https://www.lagunalites.com/https://pinemeadowsdesigns.com/https://bobdingethal.com/https://www.nonoego.com/https://www.protesisdentaljc.com/https://www.tuyetlinhdesign.com/https://www.uccuyosanjuan.com/https://advmarketingsolutions.com/https://thepetswiki.com/https://beautywebblog.com/https://onlinebrokershub.com/https://socdigest.org/https://altonmuseum.com/https://millionsaver.com/https://hotelclubz.com/https://ginzafusou.com/https://solomonrugs.net/https://summithill.net/https://arishit.com/https://www.ayusastra.com/https://www.chrisgordonclark.com/https://indianpilotsguild.org/https://pinecrestoc.com/https://www.piedringnecksusa.com/https://www.hitmovieswatch.com/https://habaneroco.com/https://humbleguide.net/https://hakimmarket.com/https://duslervekabuslar.com/https://www.lauraslistpodcast.com/https://hermes-belts.com/https://mamatoto.it.com/https://www.socalmagicians.com/https://hellosouthbend.com/https://amtexmall.com/https://boscaioli.com/https://bloodybanana.com/https://brisasdevalencia.com/https://billingfrance.com/https://claptonite.com/https://capoeirausa.com/https://bestbritishfoods.com/https://kisihidup.com/https://bradcoweb.com/https://gardengroupzambia.com/https://basketrivasecopolis.com/https://blazeappin.com/https://buyivermect.com/https://www.cpennyfeather.com/https://hotelstardust.org/https://cfilondon.org/https://aogoisicilia.net/https://mamatoto.it.com/https://artsonetlumiere.com/https://celestiqforum.com/https://cenforeds.com/https://bluemerry.com/https://eagerbug.com/https://eastsidefilm.com/https://topchristianlouboutinf.com/https://www.frannielindsay.net/https://informasesso.com/https://killersitesdesign.com/https://chaophrayafilm.com/https://mardevela.com/https://equitygrowthinsight.com/https://capturedvows.com/https://berettagunshop.com/https://www.yenimuhit.com/https://p200m.it.com/https://mahjong88.it.com/https://kokototo.it.com/https://opaltoto.it.com/https://koinhoki88.it.com/https://pasti123.it.com/https://vip555.it.com/https://evohoki.it.com/https://slot123.it.com/https://988slot.it.com/https://mamatotovillage.online/https://camar4444.store/https://mamatoto.online/https://djarumtoto.cv/https://naga888.it.com/https://naga99r.net/https://www.jarumtoto.it.com/https://jarumtoto2.com/https://www.digitalheptagon.co/https://www.gadgetunivers.com/https://www.lahydra.com/https://mamatoto.it.com/https://proqq.it.com/https://superabbit77.it.com/https://pinecrestoc.com/https://humbleguide.net/https://www.yenimuhit.com/https://www.judykapner.com/gallery/https://prod.cocorahs.org/about/https://prod.cocorahs.org/https://www.ayusastra.com/https://www.suzannesmithactress.com/http://www.biologiainteresante.com/https://www.capturedvows.com/https://www.blazeappin.com/https://www.equitygrowthinsight.com/https://basketrivasecopolis.com/https://mardevela.com/https://kisihidup.com/https://duslervekabuslar.com/https://billingfrance.com/https://capoeirausa.com/https://www.hitmovieswatch.com/https://indianpilotsguild.org/https://claptonite.com/https://buyivermect.com/https://habaneroco.com/https://amtexmall.com/https://coolchatter.com/https://zorototo.it.com/https://djarumtotovillage.org/https://aurampologin.com/https://www.neighbourfood.ie/https://www.mis.spark-online.org/https://societyfia.org/journal/include/fyp/